A Cohort Analysis of Postbariatric Panniculectomy—Current Trends in Surgeon Reimbursement. Issue 1 (January 2016) - Aherrera, Andrew S.; Pandya, Sonal N.
Abstract : Background: The overall number of patients undergoing body contouring procedures after massive weight loss (MWL) has progressively increased over the past decade. The purpose of this study was to evaluate the charges and reimbursements for panniculectomy after MWL at a large academic institution in Massachusetts. Methods: A retrospective review was performed and included all identifiable panniculectomy procedures performed at our institution between January 2008 and January 2014. The annual number of patients undergoing panniculectomy, the type of insurance coverage and reimbursement method of each patient, and the amounts billed and reimbursed were evaluated. Results: During our study period, 114 patients underwent a medically necessary panniculectomy as a result of MWL. The average surgeon fee billed was $3496 ± $704 and the average amount reimbursed was $1271 ± $589. Ten cases (8.8%) had no reimbursements, 31 cases (21.8%) reimbursed less than $1000, 66 cases (57.9%) reimbursed between $1000 and $2000, and no cases reimbursed the full amount billed. When evaluated by type of insurance coverage, collection ratios were 37.4% ± 17.4% overall, 41.7% ± 16.4% for private insurance, and 24.0% ± 13.0% for Medicare/Medicaid insurance ( P < 0.001). Conclusions: Reimbursements for panniculectomy are remarkably low, and in many instances, absent, despite obtaining previous preauthorization of medical necessity. Although panniculectomy is associated with improvements in quality of life and high levels of patient satisfaction, poor physician reimbursement for this labor intensive procedure may preclude access to appropriate care required by the MWL patient population.